2021
DOI: 10.2196/20520
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mobile Lifestyle Intervention App as an Early Intervention for Adolescents With Obesity: Single-Cohort Study

Abstract: Background Effective, resource-efficient treatment is urgently needed to address the high rates of pediatric and adolescent obesity. This need has been accelerated by the COVID-19 pandemic. The use of a mobile health tool as an early intervention before a clinic-based multidisciplinary weight management program could be an effective treatment strategy that is appropriate during a pandemic. Objective This study aims to assess the effectiveness of and ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The studies focused on obesity prevention and treatment in many diverse populations that ranged in age, socioeconomic background, and physical status (ie, pregnancy and post partum). App features included physical activity tracking [ 69 - 78 ], food tracking [ 70 , 72 - 83 ], knowledge, education, or recommendations [ 70 , 72 - 76 , 78 , 79 , 82 - 86 ], push notifications or scheduled reminders [ 74 - 76 , 78 , 79 , 81 - 84 , 86 ], weight monitoring [ 75 , 76 , 78 , 81 , 85 , 86 ], behavior demonstration [ 69 , 75 , 83 ], motivational challenges [ 69 , 75 - 78 , 83 ], goal setting [ 69 , 73 - 75 , 78 , 81 , 84 , 85 ], feedback [ 69 , 70 , 73 , 75 , 76 , 81 - 83 , 86 ], community support [ 70 , 75 , 78 , 85 ], connectivity to digital health devices [ 70 , 72 , 81 , 86 ], clinician portals [ 72 , 73 , 82 ], and access to a health coach [ 76 - 78 ...…”
Section: Resultsmentioning
confidence: 99%
“…The studies focused on obesity prevention and treatment in many diverse populations that ranged in age, socioeconomic background, and physical status (ie, pregnancy and post partum). App features included physical activity tracking [ 69 - 78 ], food tracking [ 70 , 72 - 83 ], knowledge, education, or recommendations [ 70 , 72 - 76 , 78 , 79 , 82 - 86 ], push notifications or scheduled reminders [ 74 - 76 , 78 , 79 , 81 - 84 , 86 ], weight monitoring [ 75 , 76 , 78 , 81 , 85 , 86 ], behavior demonstration [ 69 , 75 , 83 ], motivational challenges [ 69 , 75 - 78 , 83 ], goal setting [ 69 , 73 - 75 , 78 , 81 , 84 , 85 ], feedback [ 69 , 70 , 73 , 75 , 76 , 81 - 83 , 86 ], community support [ 70 , 75 , 78 , 85 ], connectivity to digital health devices [ 70 , 72 , 81 , 86 ], clinician portals [ 72 , 73 , 82 ], and access to a health coach [ 76 - 78 ...…”
Section: Resultsmentioning
confidence: 99%
“…One study reported significant increase in the average weekly steps over the course of the intervention, however, the average mood state (positive and negative) remained the same 22 . Another study reported no significant changes in the time spent engaging in moderate to vigorous exercise and their emotional functioning immediately post‐intervention, whereas they found these measures reached significance at the 6‐month follow‐up 21 …”
Section: Resultsmentioning
confidence: 97%
“…Huang and colleagues 19 set their physical activity goals to engage in at least 1 h of "moderate-to-vigorous" physical activity, as well as a daily 15,000-step goal, whilst Chew and colleagues 21 recommended their participants to work towards 60 min of moderate to vigorous physical activity each day.…”
Section: Exercise Interventions Delivered Onlinementioning
confidence: 99%
See 2 more Smart Citations